2010
DOI: 10.1260/1757-482x.2.4.189
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling of Electrostatic Forces in Gas-Solid Fluidized Beds

Abstract: Electrostatic charges in gas-solid fluidized beds are known to influence the bed dynamics, bubble shape and size, particle agglomeration, segregation and entrainment. In practice, accumulation of electrostatic charges in fluidized beds can lead to operational issues. The present work

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…2 displays the instantaneous contours of solid volume fraction with unlike charges. At the boundary of the two solid phases, the positively and negatively charged particles attracted each other, driving the particles at both sides to move and assemble towards the square centerline, in agreement with the literature results [24,51]. This testing case showed that the electrostatic model in this work was able to capture the important basic electrostatic phenomenon.…”
Section: Verification Of Electrostatic Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…2 displays the instantaneous contours of solid volume fraction with unlike charges. At the boundary of the two solid phases, the positively and negatively charged particles attracted each other, driving the particles at both sides to move and assemble towards the square centerline, in agreement with the literature results [24,51]. This testing case showed that the electrostatic model in this work was able to capture the important basic electrostatic phenomenon.…”
Section: Verification Of Electrostatic Modelsupporting
confidence: 90%
“…Numerical simulation provides a viable alternative to study the electrostatic effects in gas-solid fluidized bed. Rokkam et al [2,24] used the Eulerian-Eulerian multi-fluid model coupled with electrostatic model to simulate the bipolar charging phenomenon in a gas-solid fluidized bed. The magnitude of electrostatic force was calculated based on the Lorentz force equation.…”
Section: Introductionmentioning
confidence: 99%
“…9. Instantaneous contours of (a) electric potential, (b) total solids volume fraction at the center and along the bed height at t = 100 s. that sufficiently high charges on the solid phase can cause agglomeration and defluidization in gas-solid fluidized beds [73].…”
Section: Effect Of Charge On the Spatial Distribution Of Polymer Partmentioning
confidence: 99%
“…Electrostatic charge generation is known to affect the bubble dynamics such as size, shape and also particle elutriation rates (Rokkam et al, 2010). With charge accumulation, process upsets such as defluidization can occur (Hendrickson, 2006;Rokkam et al, 2009;Moughrabiah et al, 2012;Sowinski et al, 2012). Understanding the dynamics of the bed aids in the design and process optimization of such reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the dynamics of the bed aids in the design and process optimization of such reactors. In this work the electrostatic model previously developed in Rokkam et al (2009Rokkam et al ( , 2010 is compared with results obtained from experiments performed by Sowinski et al (2010).…”
Section: Introductionmentioning
confidence: 99%